Regulation of Dendrobium Polysaccharides on Proliferation and Oxidative Stress of Human Umbilical Vein Endothelial Cells in the High Glucose Environment - Yajia Li; Ziqin Cao; Limin Jia; Yanfei Huang; Meilan Shi; Qiangxiang Li (Journal of Diabetes Research, 2021)
Backgrounds. Polysaccharides of Dendrobium candidum (PDC) showed a strong antioxidant effect on islet cells while the effects of PDC on human umbilical vein endothelial cells (HUVECs) under the high glucose condition remain unclear. Material and Method. HUVECs were incubated with high glucose (33.3 mmol/L) for 48 hours to induce injury, and cells were treated with PDC (100, 200, and 400 μg/mL) for 48 hours. The tetrazolium blue colorimetric (MTT) assay was used to detect cell proliferation, superoxide dismutase (SOD), and nitric oxide (NO) content in cell supernatants. Flow cytometry was used to detect reactive oxygen species (ROS) and calcium levels. Results. (1) Compared with the control group, the proliferation of HUVECs cells in the high glucose (33.3 mmol/L) group decreased (P<0.05). The intracellular calcium ion concentration and the intracellular ROS level increased (P<0.01 and P<0.05). SOD activity and the level of NO in the culture medium were reduced (P <0.05). (2) Compared with the control group, PDC (50, 100, 200, 400, and 800 μg/mL) did not significantly affect the cell proliferation of HUVECs (P>0.05). (3) Compared with the high glucose group, the HUVEC cell viability of the high glucose + PDC (100, 200, and 400 μg/mL) group increased while the intracellular calcium ion concentration decreased in a concentration-dependent manner (P<0.05). Intracellular ROS levels were reduced, while SOD activity and the level of NO in culture fluids increased (P<0.05). Conclusion. PDC can promote the proliferation of HUVECs in the high glucose environment by reducing oxidative stress injury of HUVECs induced by high glucose.